3D Carbon Electrocatalysts In Situ Constructed by Defect‐Rich Nanosheets and Polyhedrons from NaCl‐Sealed Zeolitic Imidazolate Frameworks. (19th January 2018) - Wang, Yuqing; Tao, Li; Xiao, Zhaohui; Chen, Ru; Jiang, Zhongqing; Wang, Shuangyin
Abstract: The proper structure design and defect engineering are of essential importance to develop advanced electrocatalysts for the oxygen reduction reaction (ORR), which is a critical reaction in both fundamental science and industrial applications. Herein, a three‐dimensional carbon electrocatalyst is prepared by in‐situ linking carbon polyhedrons with nanosheets through high‐temperature pyrolysis of metal‐organic frameworks (MOFs) confined in a salt‐sealed reactor. In the transformation to polyhedrons, the organic species partially decompose and form carbon nanosheets due to being confined in the salt reactor. The in ‐situ‐formed carbon nanosheets surround the carbon polyhedrons to form a 3D carbon network. Due to the confinement effect, the transformation of MOFs to carbon networks in the salt reactor is of high yield without significant loss of active carbon species, which would enhance the electron and mass transport for electrocatalysis. More interestingly, the as‐prepared 3D nanosheet‐linked‐polyhedron carbon (NLPC) is defect‐rich with high N‐doping levels and enriched active sites for electrocatalysis. With enhanced mass, electron transport, and enriched active sites, the material shows excellent activity as ORR electrocatalyst which is even comparable with Pt/C. The primary zinc‐air batteries assembled by the NLPC as the cathode also show outstanding performance. Abstract : 3D carbon electrocatalysts is constructed by in situ linking carbon polyhedrons with nanosheets from metal‐organic frameworks in a salt (NaCl) confined reactor. The 3D macroscopic structure contributes to the enhanced mass diffusion, the nanosheet linking increases the electronic conductivity, and the high N doping and the rich defects provide abundant active sites for oxygen reduction reaction.